Outcome Assessment of a Writing Skill Improvement Initiative for Management Graduates. (3rd October 2017) - Deepa, R.; Gayathridevi, K. Sri
ABSTRACT: This study aims to show the effectiveness of a writing skill improvement initiative adopted in a Managerial Communication course. The sample included all students who enrolled in the Master of Business Administration program. Pre-post measurement format was adopted to assess the outcome of the course. The paper also discusses the outline of the course, delivery, assessment and feedback process. The results showed that the initiative was successful in improving the writing skills of the students. The study also offers suggestions to tackle the challenges faced by business schools, faculty, and students with regard to improving the writing skills of business graduates.